Age related prevalence of hepatitis G virus in South Africans. Issue 10 (1st October 1999) - Mphahlele, M J; Aspinall, S; Spooner, R; Carman, W F
Abstract : AIM: To investigate the age related prevalence of hepatitis G virus (HGV) infection and its mode of transmission in relation to hepatitis B (HBV) and C (HCV) co-infection in South African blacks. METHODS: Reverse transcriptase polymerase chain reaction was performed to detect active infection, using primers for the 5'-NCR, NS5a, and NS3 regions. Antibodies to HGV envelope-2 protein (anti-E2), which measures past infection, were also sought. RESULTS: The overall prevalence of active infection was 116/580 (20%). A higher prevalence was noted in HBsAg carriers (28/106; 26.4%) and HCV positive subjects (25/82; 30.5%). In contrast to developed countries, active and past infection was seen in 12.9% and 12.1% of the general population, respectively (subjects negative for HBsAg and anti-HCV markers and with normal alanine aminotransferase values), with a total prevalence of 21.1% (52/248). Viraemia and anti-E2 were almost mutually exclusive. The distribution of viraemia by age was: < or = 15 years, 20/223 (9.0%); 16-35 years, 42/147 (28.6%); > or = 36 years, 37/151 (24.5%), with a significant difference (p = 0.001) in age related prevalence. A similar trend was observed for the prevalence of past infection in the general population. CONCLUSIONS: HGV infection begins in childhood and increases with age in South Africa, but transmission is largely independent of HBV and HCV. No association was found between HGV viraemia and hepatitis, or with co-infection with either HBV or HCV.